Exploring Semantic Field of Joy in TV Corpus: A Corpus-Driven Analysis of Psycho-evolutionary Theory of Basic Emotions - Shahzeb Shafi; Arbab Fatima; Muhammad Hamzah Masood; Mansoor Hassan (Al-Qanṭara, 2023)
Non-native English speakers have few language possibilities for expressing joyous feelings. Contemporary multidisciplinary research links computer science, linguistics and psychology to solve the problem. This research combines a corpora-lingual dataset of Mark Davies’ TV Corpus launched in 2019 from computer science, an Oxford Thesaurus linguistic source, and Robert Plutchik’s Psycho-evolutionary Theory of Basic Emotions from psychology. The emotion of ‘Joy’ was extracted from the English Oxford Thesaurus. Robert Plutchik’s Psycho-evolutionary Theory of Basic Emotions, presented in 1980, was applied to the TV Corpus to derive semantic fields for the emotions of joy. The descriptive mixed-method study revealed 34 lexical entries for joy. The semantic fields of pleasure, treat, joy and prize with frequencies 20908, 15532, 10572 and 6686 were the most frequent in the TV Corpus. The findings provided adequate support for TV Corpus to be used as a monitor corpus of informal spoken English, particularly for conveying emotions. Keywords: Joy, Semantic Field, TV Corpus, Oxford Thesaurus, Semantic Field, Psycho-evolutionary Theory of Basic Emotions.